Bacteria Present in Carotid Arterial Plaques Are Found as Biofilm Deposits Which May Contribute to Enhanced Risk of Plaque Rupture - Bernard B. Lanter (American Society for Microbiology, 2014)
ABSTRACT Atherosclerosis, a disease condition resulting from the buildup of fatty plaque deposits within arterial walls, is the major underlying cause of ischemia (restriction of the blood), leading to obstruction of peripheral arteries, congestive heart failure, heart attack, and stroke in humans. Emerging research indicates that factors including inflammation and infection may play a key role in the progression of atherosclerosis. In the current work, atherosclerotic carotid artery explants from 15 patients were all shown to test positive for the presence of eubacterial 16S rRNA genes. Density gradient gel electrophoresis of 5 of these samples revealed that each contained 10 or more distinct 16S rRNA gene sequences. Direct microscopic observation of transverse sections from 5 diseased carotid arteries analyzed with a eubacterium-specific peptide nucleic acid probe revealed these to have formed biofilm deposits, with from 1 to 6 deposits per thin section of plaque analyzed. A majority, 93%, of deposits was located proximal to the internal elastic lamina and associated with fibrous tissue. In 6 of the 15 plaques analyzed, 16S rRNA genes from Pseudomonas spp. were detected. Pseudomonas aeruginosa biofilms have been shown in our lab to undergo a dispersion response when challenged with free iron in vitro. Iron is known to be released into the blood by transferrin following interaction with catecholamine hormones, such as norepinephrine. Experiments performed in vitro showed that addition of physiologically relevant levels of norepinephrine induced dispersion of P. aeruginosa biofilms when grown under low iron conditions in the presence but not in the absence of physiological levels of transferrin. IMPORTANCE The association of bacteria with atherosclerosis has been only superficially studied, with little attention focused on the potential of bacteria to form biofilms within arterial plaques. In the current work, we show that bacteria form biofilm deposits within carotid arterial plaques, and we demonstrate that one species we have identified in plaques can be stimulated in vitro to undergo a biofilm dispersion response when challenged with physiologically relevant levels of norepinephrine in the presence of transferrin. Biofilm dispersion is characterized by the release of bacterial enzymes into the surroundings of biofilm microcolonies, allowing bacteria to escape the biofilm matrix. We believe these enzymes may have the potential to damage surrounding tissues and facilitate plaque rupture if norepinephrine is able to stimulate biofilm dispersion in vivo. This research, therefore, suggests a potential mechanistic link between hormonal state and the potential for heart attack and stroke.